A Critical Analysis of Structural Contradictions in Open and Distance Higher Education Using Cultural-Historical Activity Theory - K. P. Joo (Adult Education Research Conference, 2014)
Drawing upon cultural-historical activity theory, this research analyzed the structural contradictions existing in a variety of educational activities among a group of alienated adult students in open and distance higher education.